2004
DOI: 10.1590/s0080-62342004000100007
|View full text |Cite
|
Sign up to set email alerts
|

Representação social da criança sobre o câncer

Abstract: This research was motivated by the need to know more about the care of children with cancer. The objective of the study was to discover what the social representation of the child with cancer are. Ten open interviews were conducted with children and teenagers from 9 to 15 years of age. The analysis issues that emerged from the children's discourse were about the disease, the treatment, the health care workers and family relationships. The present study presents the social representation of the disease, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
(5 reference statements)
0
3
0
12
Order By: Relevance
“…Como já nos alertavam Almeida (2005) e Cagnin et al (2004, as narrativas das crianças também trazem a possibilidade da morte. A análise demonstrou que duas crianças com mais tempo de tratamento fi nalizaram suas histórias com a morte de seus personagens.…”
Section: Resultsunclassified
“…Como já nos alertavam Almeida (2005) e Cagnin et al (2004, as narrativas das crianças também trazem a possibilidade da morte. A análise demonstrou que duas crianças com mais tempo de tratamento fi nalizaram suas histórias com a morte de seus personagens.…”
Section: Resultsunclassified
“…Regarding experiencing pain, significantly expressed in dramatizations, we know that to be an aspect which has been enhanced by literature. Studies on children with cancer concluded that pain is a constant in their lives, emerging from answers on diversified routine situations, as in the case of physical changes (16) , and identified cancer as a illness that causes a lot of pain (17) . Fearing the unknown, also expressed by the selected group of children during the dramatization, reinforces the importance of them to be prepared for procedures, mainly when referring to a new experience, which generate discomfort, expectation and anxiety, emotions that can be minimized through the acknowledgement of what is really going to happen next, which is the focus of the Instructional PT (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, questões referentes a esse assunto são inquietantes para ela, pois, na qualidade de "criança doente", indagase sobre seu próprio acometimento. Para a criança, o acometimento pelo câncer é permeado por sentimentos múltiplos suscitados frente a toda problemática que abarca o "estar doente" e o "fazer tratamento", o que colabora para engrandecer a importância da comunicação dos pais com a criança sobre sua doença (Cagnin, Liston, & Dupas, 2004).…”
Section: As Culpas As Faltas E As Dores: Os Significados Dados Pelosunclassified